Stopping-power calculations and the Levine-Mermin dielectric function for inner shells - Peralta, Jesica Paola (2022)
The contribution of bound electrons to the electronic stopping power is modeled by using the shellwise local plasma approximation (SLPA). An improvement to this formalism is proposed by including the Levine-Mermin dielectric function (SLPA-LM). This approach considers a more realistic description of the bound electron response by facing the problem of the damping in the collective excitations. We introduce a local damping that depends on the density of electrons of each shell, keeping the full-theoretical characteristic of the SLPA. We implement the present model to obtain the stopping power for metal targets of period-6 elements of the periodic table (Hf, Ta, W, Os, and Pt) and we analyze the importance of the SLPA-LM description of heavy multielectronic targets. Furthermore, we investigated metal targets of group VI of the periodic table (Cr, Mo, and W) to inspect the dependence of the SLPA-LM with the number of subshells.